2017
DOI: 10.1111/ele.12859
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric distribution models: ecological stoichiometry at the landscape extent

Abstract: Human activities are altering the fundamental geography of biogeochemicals. Yet we lack an understanding of how the spatial patterns in organismal stoichiometry affect biogeochemical processes and the tools to predict the impacts of global changes on biogeochemical processes. In this contribution we develop stoichiometric distribution models (StDMs), which allow us to map spatial structure in resource elemental composition across a landscape and evaluate spatial responses of consumers. We parameterise StDMs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 76 publications
(114 reference statements)
5
98
0
Order By: Relevance
“…Similarly to our approach, the StDMs also fitted generalized linear regression models between elemental response variables and covariates. According to their results, StDMs will allow researchers to map element resources across geographic spaces and hold the promise of describing geographical patterns in organismal elemental traits at various spatial extents (Leroux et al, 2017). In this study, we found that the R 2 of the MLR models are high (Table 1), further supporting the reliability of MLR models in spatial estimation of elemental concentrations and stoichiometric ratios.…”
Section: Reliability Of Mlr Modelssupporting
confidence: 71%
See 4 more Smart Citations
“…Similarly to our approach, the StDMs also fitted generalized linear regression models between elemental response variables and covariates. According to their results, StDMs will allow researchers to map element resources across geographic spaces and hold the promise of describing geographical patterns in organismal elemental traits at various spatial extents (Leroux et al, 2017). In this study, we found that the R 2 of the MLR models are high (Table 1), further supporting the reliability of MLR models in spatial estimation of elemental concentrations and stoichiometric ratios.…”
Section: Reliability Of Mlr Modelssupporting
confidence: 71%
“…In contrast, our study not only confirmed the general variations in the concentrations of elements and their stochiometric ratios but also provided the spatial patterns or variations of the concentrations and stochiometric ratios based on the data derived from sampling sites. In fact, these spatial patterns are more useful for a better understanding of the regional biological and ecological processes corresponding to soil chemical characteristics (Prater et al, 2017;Leroux et al, 2017).…”
Section: Comparison Between Measured and Modeled Valuementioning
confidence: 99%
See 3 more Smart Citations